PROTOTYPE OF CONTROL AND MONITORING OF LAMP CONDITION, LUMEN AND BOX ANGLE PRECISION APPROACH PATH INDICATOR (PAPI) BASED ON GSM - Faisol Hidayat, Mochammad; Indrianto Sudjoko, Rifdian; Junipitoyo, Bambang (Proceeding of International Conference of Advanced Transportation, Engineering, and Applied Social Science, 2023)
Precission Approach Path Indicator (PAPI) is one of the visual aircraft landing aids in the form of lighting lamps that function to assist aviators when landing on the runway in order to land efficiently and safely. Precission Approach Path Indicator (PAPI) has an important role during the aircraft landing process, so a control and monitoring system is needed as an alternative way or another option in monitoring the condition, lumen and angle of the Precission Approach Path Indicator (PAPI) lamp. This research prototype uses the Arduino Mega microcontroller as data processing obtained from the ACS712 current sensor which detects whether or not the lamp is on the Precission Approach Path Indicator (PAPI), the BH1750 lumen sensor detects if the PAPI lamp has decreased light intensity past its minimum limit, and the MPU6050 angle sensor which detects if there is a change in the angle of the Precission Approach Path Indicator (PAPI) box and later the GSM SIM800L will send an SMS message to the technician’s cellphone that a problem has occurred. This tool can also control the disconnection or connection of PAPI lights via SMS commands. The results of research on this prototype tool control system can work to turn on or turn off PAPI lights only by sending SMS messages via cellphone with an average delay time of 2 seconds after the message is sent. The monitoring system can also work well, namely when a trouble maker is carried out on each sensor, the cellphone receives an SMS message by displaying the sequence of PAPI lights that are experiencing problems. With the results of this research, it is hoped that technicians can be helped and flight operations can run well